Degradation of apoptotic cells - Nagata, Shigekazu (Henry Stewart Talks, 2007)
Apoptosis, DNA fragmentation during apoptosis, DNA degradation in macrophages, Activation of innate immunity by undigested DNA, Engulfment of apoptotic cells, Phosphatidylserine-dependent engulfment of apoptotic cells, Autoimmune disease caused by unengulfed apoptotic cells
Archived at 2021/02/25